Risk sharing, benefit distribution and cooperation longevity: Sustainable development of dairy farmer cooperatives in China - Zhong, Zhen; Jia, Fu; Long, Wenjin; Chen, Kevin Z. (Informa UK Limited, 2022)
The sustainable development of cooperatives is essential to agricultural sustainability and is determined mainly by cooperation longevity. The risk sharing and benefit distribution mechanisms are important governance arrangements that affect cooperation longevity in member-heterogeneous cooperatives. However, the relationship between cooperatives’ risk sharing and benefit distribution arrangements and cooperation longevity is not well understood. To address this research gap, we provide a conceptual framework to illustrate the relationship between risk sharing, benefit distribution, contract form and cooperation longevity. By conducting 23 interviews with three dairy cooperatives in China using a multiple-case-study method, we find that cooperation longevity is influenced by the alignment of the combination of risk sharing and benefit distribution for cooperatives and their members. Following the principles of risk-benefit equivalence and strategy-risk preference matching, we discuss four scenarios of match or mismatch of combinations of risk sharing and benefit distribution. We suggest that the government needs to strengthen risk mitigation capabilities for cooperatives and members, and to help them to build an effective risk sharing and benefit distribution arrangement to achieve sustainable development.